2012
DOI: 10.1038/bjc.2012.24
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of EMT phenotype in the gefitinib-resistant cells of a head and neck squamous cell carcinoma cell line through Akt/GSK-3β/snail signalling pathway

Abstract: Background:Epithelial mesenchymal transition (EMT) is known to be associated with chemoresistance as well as increased invasion/metastasis. However, the relationship between EMT and resistance to an epidermal growth factor receptor (EGFR) -targeting drug in head and neck squamous cell carcinoma (HNSCC) remains unknown. In this study, we investigated the acquisition of EMT by gefitinib in HNSCC cell line (UMSCC81B).Methods:We isolated fibroblastoid variant (81B-Fb) from gefitinib-resistant UMSCC81B-GR3 cells ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
61
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 29 publications
10
61
0
Order By: Relevance
“…AKT induces activation of GSK-3β, which in turn suppresses phosphorylation of Snail to induce EMT. Participation of Akt/GSK-3 β /Snail pathway in the acquisition of EMT phenotype has been reported previously [62]. In this study, FSS up-regulated both Snail and Slug, that may suppress the expression of E-cad and promote EMT.…”
Section: Discussionsupporting
confidence: 79%
“…AKT induces activation of GSK-3β, which in turn suppresses phosphorylation of Snail to induce EMT. Participation of Akt/GSK-3 β /Snail pathway in the acquisition of EMT phenotype has been reported previously [62]. In this study, FSS up-regulated both Snail and Slug, that may suppress the expression of E-cad and promote EMT.…”
Section: Discussionsupporting
confidence: 79%
“…This observation is in accordance with studies of pancreatic and colon cancer cells [9,28] . Inhibition of Akt activity by the down-regulation of pAkt can decrease pGSK-3β levels, while activation of Akt might phosphorylate GSK-3β [31] . Meanwhile, using an Akt inhibitor leads to β-catenin repression, which is similar to observations made using Gal-3-siRNA.…”
Section: Discussionmentioning
confidence: 99%
“…1 Enhanced genome instability with gross chromosomal abnormalities has been directly correlated with tumor recurrence and metastasis of NPC, 2,3 leading to high mortality and low five-year overall survival, which have not been improved in decades. 4 Understanding of the molecular mechanisms involved in the development of advanced head and neck cancers will help in clinical management and drug discovery. Genome-wide surveys and clinical association studies have identified two recurrent copy-number aberrations, 3p deletion (3p12.3-p14.2) and 3q amplification (3q26.2--26.32), with prognostic value for metastatic NPC.…”
Section: Introductionmentioning
confidence: 99%